An introduction to the law of contracts in some common law African countries - Chukwuma Romanus, Ejim (Utrumque ius, 2016)
The aim of this work is to provide a general introduction to the law of contracts in some common law African countries. It tries to give a general idea of the law of contracts as seen in Botswana, Ghana, Kenya and Nigeria. It follows the line of history in order to explain how the contemporary law of contracts in these countries came to be received, developed, interpreted and applied in concrete court cases. It is written to supply the needed fundamentals of contract laws in the contemporary African customary laws, that is, laws, rules, regulations, statutes, legislations handed down by these common law African countries. It invites university students interested in the law of contracts in African common law countries; lawyers and students of law who need to understand African legal systems, and those of them who deal with African customary laws in general; buisness people, government officials and all those whose work regularly involves contracts and the laws guiding it; general readers who recognize the need for knowlegde acquisition regarding contract laws in common law African countries, who have never done any course on law to lay their hands on this work.